Chapter 10 Gender Identity and Leadership - Laraque-Ho, Rivers (Taylor & Francis, 2023)
This case study, written by a recent college graduate, brings the perspective of a generation educated in the 21st century, relevant to gender identity, its ﬂuidity, shedding prior concepts of gender and leadership.